Model Kesetiaan Pelanggan Toko Daring - Chofifah Mutiara Putri; Waluyo Budi Atmoko; Sugiyarmasto Sugiyarmasto (Politeknik Kampar, 2023)
Online customer loyalty is important to ensure continuity of purchases at online stores. The study aims to explore and test the significance of a number of constructs in an effort to predict online customer loyalty. Literature studies suggest that online customer loyalty is closely related to the constructs of online customer satisfaction, online customer trust, and online service quality. The research was conducted using a survey design. The population and sample were online store customers. Sample data of 200 respondents were collected using purposive sampling technique and analyzed by structural equation modeling. The results of the study are: (1) online service quality affects online customer satisfaction, (2) online service quality affects online customer trust, (3) customer satisfaction has no significant effect on customer loyalty to shop at online stores, (4) online customer trust has a significant effect on online customer loyalty. The results of this study are important for online store managers in an effort to build customer loyalty.